2004
DOI: 10.1097/01.sla.0000130850.31178.8c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Biliary Diversion Procedure on Carcinogenesis in Barrett??s Esophagus Surgically Induced by Duodenoesophageal Reflux in Rats

Abstract: It is likely that the converting procedure from the esophagojejunostomy to induce DER to biliary diversion does not lead to regression of BE but prevents the development of esophageal adenocarcinoma in the rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 46 publications
4
70
1
3
Order By: Relevance
“…Esophagitis occurs in patients who have undergone total gastrectomy without biliary diversion and in patients with achlorhydria (Helsingen, 1961;Orlando and Bozymski, 1973;Palmer, 2002;Yumiba et al, 2002;Sandvik and Halvorsen, 1988). Barrett's esophagus has been described after total gastrectomy with esophagojejunostomy (Nishijima et al, 2004). This supports the view that NAR, represented by the reflux of duodenal contents alone, has a role in esophageal mucosal injury.…”
Section: Pathological Refluxsupporting
confidence: 64%
See 2 more Smart Citations
“…Esophagitis occurs in patients who have undergone total gastrectomy without biliary diversion and in patients with achlorhydria (Helsingen, 1961;Orlando and Bozymski, 1973;Palmer, 2002;Yumiba et al, 2002;Sandvik and Halvorsen, 1988). Barrett's esophagus has been described after total gastrectomy with esophagojejunostomy (Nishijima et al, 2004). This supports the view that NAR, represented by the reflux of duodenal contents alone, has a role in esophageal mucosal injury.…”
Section: Pathological Refluxsupporting
confidence: 64%
“…DGER was more harmful than GOR with higher percentage of adenocarcinoma. Nishijima et al (2004) created three different models for reflux: gastrectomy plus esophago-jejunostomy, gastrectomy plus esophago-duodenostomy and gastrectomy plus Roux-en-Y anastomosis. They concluded that esophago-jejunostomy procedure does not cause regression of Barrett's esophagus but prevents the development of adenocarcinoma.…”
Section: What We Have Learned From Animal Reflux Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 The operation was, therefore, modified to include the Roux-en-Y anastomotic technique, 38 which has the added advantage of decreasing biliary reflux and preventing subsequent gastric cancer risk. 39,40 The vast majority of procedures are performed laparoscopically 41 and demonstrate low postoperative adverse outcomes. A recent multicenter, prospective, observational study 42 revealed an overall operative 30-day mortality to be 0.3%.…”
mentioning
confidence: 99%
“…37 The formation of DYS or CLE is regarded as an early stage in carcinogenesis and is an irreversible change. 31,38 The persistent inflammation because of duodenal reflux may promote the process from DYS to SCC or CLE to ADC. Therefore, earlier administration of a selective COX-2 inhibitor could be more effective in preventing this carcinogenesis.…”
mentioning
confidence: 99%